2023
DOI: 10.1002/jev2.12318
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein CD147 defines miRNA‐enriched extracellular vesicles that derive from cancer cells

Abstract: Extracellular vesicles (EVs) are ideal for liquid biopsy, but distinguishing cancer cell‐derived EVs and subpopulations of biomarker‐containing EVs in body fluids has been challenging. Here, we identified that the glycoproteins CD147 and CD98 define subpopulations of EVs that are distinct from classical tetraspanin + EVs in their biogenesis. Notably, we identified that CD147 + EVs have substantially higher microRNA (miRNA) content than tetraspanin + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 82 publications
1
21
0
Order By: Relevance
“…However, these tetraspanins are ubiquitously expressed ( Maecker et al, 1997 ). A recent study traced the cellular origin of circulating CD9-positive EVs in mice bearing human cervical and renal cancer xenografts and found that the majority (i.e., approximately 70%) of CD9-positive EVs derive from mouse host cells ( Ko et al, 2023 ).…”
Section: Distinguishing Evs That Derive From Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these tetraspanins are ubiquitously expressed ( Maecker et al, 1997 ). A recent study traced the cellular origin of circulating CD9-positive EVs in mice bearing human cervical and renal cancer xenografts and found that the majority (i.e., approximately 70%) of CD9-positive EVs derive from mouse host cells ( Ko et al, 2023 ).…”
Section: Distinguishing Evs That Derive From Cancer Cellsmentioning
confidence: 99%
“…The glycoprotein CD147 (also known as EMMPRIN or basigin) is one of the most frequently detected proteins in EVs ( Ko et al, 2023 ) and is expressed in at least 25 types of cancers of diverse origin ( Supplementary Table S1 ). CD147 is also expressed in some types of normal cells such as renal tubular epithelial cells, leukocytes, platelets, and endothelial cells ( Kosugi et al, 2015 ).…”
Section: Distinguishing Evs That Derive From Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms proposed to be involved in this have been contentious, including whether the ability of CD147 to regulate MMPs is independent from its role as an MCT chaperone ( Schneiderhan et al, 2009 ). CD147 can reside in the plasma membrane, as well as in subcellular compartments, and can be released from cells in various forms ( Albrechtsen et al, 2019 ; Grass and Toole, 2015 ; Egawa et al, 2006 ; Taylor et al, 2002 ; Ko et al, 2023 ). The relation between CD147 glycosylation state, localization and function is incompletely understood, and both high-glycosylated (HG) and low-glycosylated (LG) forms of CD147 have been suggested to have the capacity for activating MMPs, although the HG form might do so more effectively ( Huang et al, 2013 ; Bai et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms involved have been contentious, including whether the ability of CD147 to regulate MMPs is independent from its role as an MCT chaperone (Schneiderhan et al, 2009). CD147 can reside in the plasma membrane, in subcellular compartments, and can be released from cells in various forms (Albrechtsen et al, 2019, Grass and Toole, 2015, Egawa et al, 2006, Taylor et al, 2002, Ko et al, 2023. The relation between CD147 glycosylation state, localization and function is incompletely understood, with both high-(HG) and low-glycosylated (LG) CD147 suggested to have the capacity for activating MMPs, although the HG form may do so more effectively (Huang et al, 2013, Bai et al, 2014.…”
Section: Introductionmentioning
confidence: 99%